Zur thermisch-hygrischen Gliederung des Mount Kenya - Winiger, Matthias (ERDKUNDE, 1981)
Soil temperatures (annual means in 50-70 cm depth) and mean annual rainfall data are the elements of the thermal-hygric zoning of Mt. Kenya, which is discussed with reference to its climatic causes as well as its ecological consequences. Soil temperatures along the profile from the lowlands to the summit, show - depending on the general exposure and altitude - distinct zones of excesses or deficiencies respectively: temperature depressions coincide with zones of frequent and dense cloud cover (producing high annual amounts of rainfall), whereas relatively high temperatures occur in areas with high solar irradiation and only little rain. Furthermore, there is clear evidence of the dominant influence of the atmospheric circulation and its local effects (dominant air currents of the free atmosphere, daily and annual course of cloudiness and local wind systems). Altitudinal belts of morphodynamic processes, the amount of vegetation coverage and vegetation itself are determined to a great extent - but not exclusively - by the mean thermal and hygric conditions. Additional local factors may further differentiate the ecological patterns (topography, soils, annual amount of frost changes, seasonal distribution of precipitation). Altogether it can be concluded that areas above 3500-4000 m are predominantely arranged by thermal limits, whereas the lower parts are equally influenced by temperature and humidity. In this contribution the following altitudinal belts are differentiated: 1. Nival zone with soil temperatures (Ts) <1°C. Seasonal frost or even permafrost (?) could be found above 4800 m. 2. Periglacial belt (vegetation coverage < 50%): Ts = l to 5,5°C, 250-300 days of frost change per year. 3. Afro-alpine belt with distinct vertical overlap of the different ecological units Ts = 5,5-8,5 °C. In areas with annual precipitations of >1250-1500 mm the tussock grassland forms proper moorlands. 4. Afro-montane belt: forests between Ts = 8,5-18 °C and with precipitation >900 mm; included a thermally well defined bamboo-zone at Ts =12-14 °C and rainfall >1200 mm. In areas withless than 900 mm annual rainfall grass- and bushland is predominant. The upper timber line concentrates at soil temperatures of Ts = 8-9°C (extremes at 7, resp.11°C), whereas other authors mention Ts=7°C as a typical value. The annual number of frost changes is estimated to be approximately 100. The lower timber line is the result of the lack of humidity or human activities. A comparison of thermal conditions at the upper timber line in tropical high mountain areas of East Africa, Central and South America and Borneo show their similarity: with the exceptions of Mt. Cameroon and Pico de Orizaba timber lines are all limited within the same thermal range as on Mt. Kenya. This contribution ends with reference to possible interpretations of the thermal-hygric data related to climato-ecological changes.